2006
DOI: 10.1111/j.1365-2583.2006.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the activities of the medfly and Drosophila hsp70 promoters in vivo in germ‐line transformed medflies

Abstract: The promoter of the hsp70 gene of Drosophila melanogaster has been widely used for the expression of foreign genes in other insects. It has been generally assumed that because this gene is highly conserved, its promoter will function efficiently in other species. We report the results of a quantitative comparison of the activities of the medfly and D. melanogaster hsp70 promoters in vivo in transformed medflies. We constructed transformed lines containing the lacZ reporter gene under the control of the two pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…In agreement with previous medfly transformation experiments (Christophides et al, 2000;Kalosaka et al, 2006), we observed strong chromosomal position effects and promoter interference phenomena as can be seen from the vari-Archives of Insect Biochemistry and Physiology January 2008 doi: 10.1002/arch. ability of β-galactosidase levels and eye coloration among the P L -lacZ lines (Table 3).…”
Section: Functional Analysis Of the Proximal Promoter Region Of Cchspsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous medfly transformation experiments (Christophides et al, 2000;Kalosaka et al, 2006), we observed strong chromosomal position effects and promoter interference phenomena as can be seen from the vari-Archives of Insect Biochemistry and Physiology January 2008 doi: 10.1002/arch. ability of β-galactosidase levels and eye coloration among the P L -lacZ lines (Table 3).…”
Section: Functional Analysis Of the Proximal Promoter Region Of Cchspsupporting
confidence: 92%
“…On the other hand, the -380/+139 region of the gene drove significant lacZ expression under normal conditions, indicating that the responsible sequences for the constitutive expression of the Cchsp83 gene reside in the interval between positions -380 and -86. The activity of this Cchsp83 promoter region is similar to the heat-inducible activity of the medfly hsp70 promoter (Kalosaka et al 2006). However, as was shown in Figure 5, the levels of constitutive expression of the lacZ RNA in two P L -lacZ lines with moderate expression were significantly lower than the respective levels of the Cchs83 RNA.…”
Section: Functional Analysis Of the Proximal Promoter Region Of Cchspmentioning
confidence: 69%
See 1 more Smart Citation
“…Similar experience has recently been described for the tephritid fruit fly Ceratitis capitata [80,81]. On the other hand, Drosophila heat shock constructs have been shown to work in the silkworm Bombyx mori [46] and the butterfly Bicyclus anynana [52].…”
Section: Discussionmentioning
confidence: 65%
“…In Drosophila and other Diptera, three to seven inducible hsp70 genes have been identified, organized at one or two chromosomal loci (for a review and references therein, see Bettencourt and Feder 2001;Evgen'ev et al 2004). The promoter of the Drosophila melanogaster hsp70 gene has been used in genetic transformation systems for conditional expression of several genes in a variety of insects, exhibiting, however, lower activity in nondrosophilid species including B. oleae (Komitopoulou et al 2004;Kalosaka et al 2006;Koukidou et al 2006). …”
Section: Introductionmentioning
confidence: 99%